ETHICS AND PHILOSOPHICAL DIMENSION OF INTERNATIONAL RELATIONS IN THE GLOBALIZED WORLD - Пода, Т. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article analyzes the moral foundations of international relations in globalized world, general and higher interests of humanity as a moral and legal principles of civilizational progress of mankind in the era of globalization.